Safety and hemostatic effect of recombinant activated factor VII in cirrhotic patients undergoing partial hepatectomy: A multicenter, randomized, double-blind, placebo-controlled trial - Yong Fu Shao (2018)
Background: Coagulopathy caused by cirrhosis may contribute to excessive bleeding during hepatectomy. We evaluated the hemostatic effect and safety of recombinant factor VIIa (rFVIIa) in cirrhotic patients undergoing partial hepatectomy. Methods: Patients were randomized to rFVIIa 50 or 100 μg/kg or placebo, administered intravenously 10 minutes before surgery and every second hour during surgery. The primary efficacy end points were the proportion of patients receiving red blood cell (RBC) transfusions and the amount of RBCs transfused. The RBC transfusion trigger was blood loss of 500 mL. Safety end points included thromboembolic and adverse events. Results: No statistically significant effect of rFVIIa treatment on efficacy end points was observed. Serious and thromboembolic adverse events occurred at similar incidences in the study groups. Conclusions: Using blood loss as a transfusion trigger, the efficacy of rFVIIa in reducing the requirement for RBC transfusion was not established in this study. No safety concerns were identified. © 2006 Excerpta Medica Inc. All rights reserved.